Transforming Egypt into the New Kingdom - Mourad, Anna-Latifa. (Wiesbaden)
463 sayfa
Keywords: “Egypt’s New Kingdom emerged from a period of regionalisation, when local communities had developed according to different trajectories that gave rise to diverse socio-cultural transformations. Dynamic and multifaceted, these processes involved a range of internal and external forces, some of which were influenced by cultural encounters. Indeed, those with the ‘rulers of foreign lands’, the Hyksos, have been commonly associated with the introduction of a host of ideas and entities into Egypt. However, the validity and extent of the impact of the Hyksos on the New Kingdom remain insufficiently addressed. Anna-Latifa Mourad explores these points of enquiry, but also expands its analysis in line with current theoretical understandings on the complexity of cultural encounters. Her study ascertains whether and how consistent Egyptian-Near Eastern encounters in the Middle Bronze Age influenced New Kingdom society, and culture. By assessing a range of archaeological, artistic, and textual material, it clarifies contexts of encounters as well as interrelated agents and mechanisms, questioning the fate of those ruled by the Hyksos. It elucidates the tangible and intangible effects of contact on historical, socio-political, religious, and technological developments, revealing how, amid the many processes of negotiation and change, elements from the Near East seeped into the dynamic and complex socio-cultural framework of Egypt, as it irreversibly transformed into the New Kingdom“ --